The impact of climate change on the economic growth in Australia, India and South Africa - Shuruthi, Ganesan; Sharmila Vathy, Segar; Beindya Marrisa, Maran; Wang, Yuan Ming (2020)
This article reviews the impacts of climate change on Australia, India and South Africa. Current prediction shows that climate change will mostly have limited impact on the economy in the 21st century. The paper uses variables including temperature, precipitation, arable land and foreign direct investment. We have used data from the year 2004 to 2014. These countries show the variation of developed and developing countries and how climate change embodies a vital role in affecting each country’s economic growth. Descriptive analysis of Pooled OLS, Fixed Effect Model, Random Effect Model, Hausman test and Wald test were used to determine the climate change impacts. Based on the tests, we have found significant affect shown on economic growth by arable land and precipitation. However, temperature and foreign direct investment do not show significant effects. Despite the limitations found in this research study, there is a clearer vision on the depth of impact the climate change may cause to the growth of an economy. Recommendations are guven in relation to the limitations which would guide future researchers. This outcome of this research would contribute to better understanding for those who are keen to know more about the topic studied.